Investigation of the Origin of Hueco Bolson and Mesilla Basin Aquifers (US and Mexico) with Isotopic Data Analysis - García-Vázquez, Ana Cristina; Granados-Olivas, Alfredo; Samani, Zohrab; Fernald, Alexander (2022)
An important tool to identify the origin of a groundwater resource is the use of isotopic signatures. Isotopic signatures give us the age of water and provide information as to the water’s origin, potential transit at geologic structures, source of salinization, and possible recharge points. The purpose of this study was to collect and analyze well samples to evaluate isotopic tracers (δ 18O and tritium) in the transboundary Conejos-Médanos/Mesilla aquifer located between the US and Mexico.